WAWANCARA, SEBUAH INTERAKSI KOMUNIKASI DALAM PENELITIAN KUALITATIF - Rosaliza, Mita (Universitas Lancang Kuning, 2015)
The most important process in conducting a research, particularly in a field research (field work) qualitatively is interview. Interviewing is not simple because qualitative interviewing involves many elements needed to be paid attention by a researcher. Parallel to that idea, this writing deals with some factors to be understood by a researcher who applies qualitative interview in the process of collecting primary data. This writing deals with it generally, such as the reason why the researcher has to apply qualitative interview, how to conduct that kind of research, what strength this concept provides, and what obstaclesls a researcher may face in applying it.